2017
DOI: 10.1111/plb.12529
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intraspecific diversity in Cistus L. (Cistaceae) seeds, analysed with computer vision techniques

Abstract: This work aims to discriminate among different species of the genus Cistus, using seed parameters and following the scientific plant names included as accepted in The Plant List. Also, the intraspecific phenotypic differentiation of C. creticus, through comparison with three subspecies (C. creticus subsp. creticus, C. c. subsp. eriocephalus and C. c. subsp. corsicus), as well as the interpopulation variability among five C. creticus subsp. eriocephalus populations was evaluated. Seed mean weight and 137 morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…For example, in a previous study [36, 37], the authors extracted features such as shape, color, and texture (contrast, correlation, homogeny, entropy) from wheat grains to classify their accessions. Moreover, in another study [38, 39], the authors used an elliptic Fourier descriptor and the texture feature set called Haralick's texture descriptors to characterize seeds of plants for taxonomic classification. With a representative feature extraction tool, Scale Invariant Features Transforms (SIFT), which acts as an invariant feature descriptor not only to scale but also rotation, illumination, and viewpoint, Wilf et al [40] generated codebooks for dictionary learning, and their results demonstrated the effectiveness of their approach on taxonomic classification through leaves.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a previous study [36, 37], the authors extracted features such as shape, color, and texture (contrast, correlation, homogeny, entropy) from wheat grains to classify their accessions. Moreover, in another study [38, 39], the authors used an elliptic Fourier descriptor and the texture feature set called Haralick's texture descriptors to characterize seeds of plants for taxonomic classification. With a representative feature extraction tool, Scale Invariant Features Transforms (SIFT), which acts as an invariant feature descriptor not only to scale but also rotation, illumination, and viewpoint, Wilf et al [40] generated codebooks for dictionary learning, and their results demonstrated the effectiveness of their approach on taxonomic classification through leaves.…”
Section: Reviewmentioning
confidence: 99%
“…They selected seven discriminative grain features, incorporating aspects of shape, color, and texture, and achieved greater than 99% accuracy on the grain classification task. Another group examined two taxonomic classification tasks: the Malva alliance taxa and genus Cistus taxa [38, 39]. They acquired digital images of seeds using a flatbed scanner; extracted morphometric, colorimetric, and textural seed features; and then performed taxonomic classification with stepwise linear discriminant analysis (LDA).…”
Section: Reviewmentioning
confidence: 99%
“…In particular, it has been successfully applied for Astragalus maritimus and A. verrucosus [ 20 ], Astragalus sect. Melanocercis [ 21 ] Lavatera triloba aggregate [ 22 ], Astragalus tragacantha complex [ 23 ] and Lavatera L., Malva L., and Cistus L. [ 24 , 25 ]. Linear discriminant analysis (LDA) models have proven to be effective for the discrimination and quality classification of seeds when combined with imaging techniques [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the low number of species (31 species are listed in Euro+Med PlantBase [7]), the genus Cistus is taxonomically complex [8]. Difficulties, uncertainties, and ambiguities in taxonomic classification and identification of Cistus species and subspecies arise from strong hybridisation between species, ecotypic differentiation (e.g., Cistus albidus, Cistus creticus) [2,9], morphological polymorphism of some species (e.g., C. creticus, Cistus monspeliensis) [8,9], and unclear generic boundaries and intra-generic organisation, as well as inconsistent naming of taxa as, e.g., the putative synonymous use of C. creticus, Cistus villosus, and Cistus incanus var. creticus in literature [2,10,11].…”
Section: Introductionmentioning
confidence: 99%